A Comparison of Cerebrospinal Fluid Beta-Amyloid and Tau in Idiopathic Normal Pressure Hydrocephalus and Neurodegenerative Dementias - Said HM; Kaya D; Yavuz I; Dost FS; Altun ZS; Isik AT (Clinical Interventions in Aging, 2022)
Harun Muayad Said,1 Derya Kaya,2,3 Idil Yavuz,4 Fatma Sena Dost,2,3 Zekiye Sultan Altun,5 Ahmet Turan Isik2,3 1Department of Molecular Medicine, Graduate School of Health Sciences, Dokuz Eylul University, Izmir, Turkey; 2Unit for Brain Aging and Dementia, Department of Geriatric Medicine, Faculty of Medicine, Dokuz Eylul University, Izmir, Turkey; 3Geriatric Science Association, Izmir, Turkey; 4Department of Statistics, Dokuz Eylul University, Faculty of Science, Izmir, Turkey; 5Department of Basic Oncology, Oncology Institute, Faculty of Medicine, Dokuz Eylul University, Izmir, TurkeyCorrespondence: Ahmet Turan Isik, Unit for Brain Aging and Dementia, Department of Geriatric Medicine, Faculty of Medicine, Dokuz Eylul University, Izmir, Turkey, Tel +90 232 412 43 41, Fax +90 232 412 43 49, Email atisik@yahoo.comPurpose: Idiopathic normal pressure hydrocephalus (iNPH) is the leading reversible cause of cognitive impairment and gait disturbance that has similar clinical manifestations and accompanies to major neurodegenerative disorders in older adults. We aimed to investigate whether cerebrospinal fluid (CSF) biomarker for Alzheimer’s disease (AD) may be useful in the differential diagnosis of iNPH.Patients and Methods: Amyloid-beta (Aß) 42 and 40, total tau (t-tau), phosphorylated tau (p-tau) were measured via ELISA in 192 consecutive CSF samples of patients with iNPH (n=80), AD (n=48), frontotemporal dementia (FTD) (n=34), Lewy body diseases (LBDs) (n=30) consisting of Parkinson’s disease dementia and dementia with Lewy bodies.Results: The mean age of the study population was 75.6± 7.7 years, and 54.2% were female. CSF Aβ42 levels were significantly higher, and p-tau and t-tau levels were lower in iNPH patients than in those with AD and LBDs patients. Additionally, iNPH patients had significantly higher levels of t-tau than those with FTD. Age and sex-adjusted multi-nominal regression analysis revealed that the odds of having AD relative to iNPH decreased by 37% when the Aβ42 level increased by one standard deviation (SD), and the odds of having LBDs relative to iNPH decreased by 47%. The odds of having LBDs relative to iNPH increased 76% when the p-tau level increased 1SD. It is 2.5 times more likely for a patient to have LBD relative to NPH and 2.1 times more likely to have AD relative to iNPH when the t-tau value increased 1SD.Conclusion: Our results suggest that levels of CSF Aβ42, p-tau, and t-tau, in particularly decreased t-tau, are of potential value in differentiating iNPH from LBDs and also confirm previous studies reporting t-tau level is lower and Aβ42 level is higher in iNPH than in AD.Keywords: Alzheimer’s disease, beta-amyloid 42, phosphorylated tau, Tau, frontotemporal dementia, Lewy body diseases, cerebrospinal fluid, biomarker, Parkinson’s disease dementia, dementia with Lewy body, differential diagnosis